Continued STEM Commitment in Light of 2020 Events: A Perspective From the Illinois Louis Stokes Alliance for Minority Participation - Botanga, Christopher; Blanc, Suzanne; Jones, LeRoy; Day, Michelle; Charles, Mariel (Frontiers in Education, 2021)
We evaluated the impact of the current COVID-19 pandemic and systemic racism on Underrepresented Minority (URM) students pursuing higher education in the STEM fields. Given the ongoing pandemic and the wave of protests following a series of police brutalities and systemic racism, URM students were thrown into uncharted territory. We reached out to a group of Black and Latino students who were already engaged in STEM. We began surveys and interviews by asking participants how they were doing as individuals, family and their communities. Next, participants answered questions about academic progress, challenges, and what support would be helpful. Our framework was based on a mixed-methods approach that draws on the work of Michael Patton (2014) and Veronica Thomas (2016). Qualitative data from interviews were collected to capture perceptions, experiences, and recommendations of the study participants. Data were collected in order to reach as many students as possible and to provide numerical self-assessments of student experience, progression, and obstacles. All qualitative data were coded thematically using Atlas.ti, with the goal of illuminating emerging themes, and reviewed using descriptive statistics. Themes emerging from both data sets were compared, contrasted, and integrated in order to develop consistent findings that would enhance URM student perseverance and persistence in the face of confounding adversities. This study shows that ILSAMP COVID-19 Study participants maintained a commitment to pursuing a career in STEM. The findings of this study also indicate that the participants are stressed by their immediate circumstances and by the ongoing racism of U.S. society. These students ask for additional financial, academic, and networking support during the disruptions caused by the pandemic. More specifically, students request continued advising and connection with STEM professionals who can help them envision and enact a pathway to their own careers in STEM during this tumultuous period. The study validates the importance of key elements of the national LSAMP model as reported by Clewell et al. These are: academic integration, social integration, and professional integration. In addition, it identifies several other factors that are key to student success including interventions that directly address racial trauma and economic hardship